Implications of Intensive Spatial Sampling of Broiler Litter: Characteristics and Gaseous Emissions - Miles , Dana M.; Rowe, Dennis E.; Brooks, John P. (International Journal of Poultry Science, 2017)
Objective: The purpose of the study was to gain an overall assessment of seasonal influences and location within houses on litter physical and chemical properties as well as litter gas flux in U.S. commercial broiler houses. Materials and Methods: More than 1000 litter samples as well as in situ gas flux of NH3, N2O and CO2 were collected spatially within four U.S. commercial broiler houses over a period of 4 years. Analysis of variance among the measurements was performed with season, bird age and location within the house as the sources of variation. Results: Total litter cleanout (where fertilizer is the end use) is recommended during winter where litter moisture is lower and litter total N is higher than at the end of summer flocks. At chick placement and during mid-flock, the highest NH3 losses were in the fan areas. At market age, fan area samples were extremely caked and gas volatilization was lowest. Conclusion: During the growout, NH3 gas flux could be minimized by zone litter treatments which could potentially enhance broiler productivity. The areas to treat near the end of the flock are in front of the cooling pads and in the brood and non-brood areas, where NH3 gas flux magnitude had tripled since chick placement.